Simultaneous Organic Matter and Nitrogen Removal from Piggery Slaughterhouse Wastewater Using Bioaugmented Gaslift Membrane Bioreactor. Issue 1 (8th December 2022) - Toan, Nguyen Duc; Tuyen, Nguyen Van; Hai, Pham Bang; Ha, Nguyen Thi Hoang; Anh, Do Tien; Dung, Bach Quang
Abstract: A single bioaugmentation reactor and a side‐stream gaslift membrane bioreactor combined with bioaugmentation are conducted to treat real wastewater from a centralized piggery slaughterhouse in Vietnam. The bioaugmented reactor is inoculated with heterotrophic microorganisms ( Bacillus sp.) isolated from piggery slaughterhouse wastewater. The results of a single bioaugmentation experiment show high removal efficiency of chemical oxygen demand (COD) (84.8%–97.5%) and total nitrogen (TN) (69.9%–87.2%) at loading rates of 1.28–3.89 and 0.14–0.37 kg m −3 d −1, respectively. The combined system demonstrates a significantly higher TN removal efficiency (89.0%–96.1%) ( p < 0.001), more stable flux (36.0–38.4 L m −2  h −1 ), and transmembrane pressure (0.95–1.05 bar), and better capacity of separation of solid–liquid phases compared to the single bioaugmentation. High COD and TN removal efficiency is possibly due to assimilation and simultaneous nitrification and denitrification processes. The results of this study also indicate the feasibility and propitious efficiency of the bioaugmented gaslift membrane bioreactor for piggery slaughterhouse wastewater treatment. Abstract : A single bioaugmentation reactor and a side‐stream gaslift membrane bioreactor combined with bioaugmentation are conducted to treat wastewater from a centralized piggery slaughterhouse. The combined system demonstrates a significantly higher total nitrogen removal efficiency (89.0%–96.1%), more stable flux and transmembrane pressure, and better capacity of separation of solid–liquid phases compared to the single bioaugmentation.